Review of Georgina Born and David Hesmondhalgh, eds. 2000. Western Music and Its Others: Difference, Representation, and Appropriation in Music. Berkeley: University of California Press - Fox, Aaron A. (Current Musicology, 2000)
This is an important book, and deserves attention from ethnomusicologists, historical musicologists, and students of popular culture across the disciplines. It is the first collection I am aware of to situate issues of the politics, semiotics, and cultural dynamics of musical appropriation in a broad, interdisciplinary context attentive to the theoretical projects of postcolonial and post-structuralist cultural studies. There have been several monographic studies and edited volumes in recent years that have explored some of this intellectual terrain; Gerry Farrell’s Indian Music and the West (1997) and Jonathan Bellman’s edited collection The Exotic in Western Music (1998) each approach art musics in terms of transnational appropriations and Orientalist cultural dynamics. And a wide range of work on popular music and globalization has taken up the thorny problematic of “appropriation” in terms of issues of ownership and cultural imperialism (a good example is Timothy Taylor’s 1997 Global Pop). However, the disciplinary and empirical articulations achieved in this volume are in many cases novel and, in their totality, quite progressive. Simply by virtue of its serious commitments to interweaving popular and art music subjects, “western” and “non-western” idioms and perspectives, and textual and contextual emphases, it sets a fine example for a more dialogic and less ghettoized future musicology. The volume is comprised of exceptionally strong papers from both very well known and younger scholars, and it is relatively coherent as a whole while covering a huge range of topics and issues.